# Proof on symmetry

## Homework Statement

$R$ is simmetric iff $R=R^{-1}$

## Homework Equations

$( \forall x \forall y ((x,y) \in R \rightarrow (y,x) \in R)) \leftrightarrow R=R^{-1}$

## The Attempt at a Solution

My problem is with my formulation in [2.] of the statement I have to prove.

Is that formulation right or the right one is $( \forall x \in A \forall y \in A ((x,y) \in R \rightarrow (y,x) \in R)) \leftrightarrow R=R^{-1}$?

The difference is significative, at least for my purpose. In the first case, I can prove it, in the second one, I cannot (or I am not able), so I would like to know if the second one is redundant.

Related Precalculus Mathematics Homework Help News on Phys.org
Bacle2
What is A? And, just to makesure, what is the definition of symmetric you're starting with? I know this is a standard term, but maybe your definition is slightly different?

What is A? And, just to makesure, what is the definition of symmetric you're starting with? I know this is a standard term, but maybe your definition is slightly different?
Well, that's the problem.

Given a set $A$, a relation $R$ on $A$ is symmetric if $\forall x \in A \forall y \in A(xRy \rightarrow yRx)$.

So, here we are.The formulation in [3.] should be the correct one to translate the statement in [1.] in logical terms, but - at the same time - it is problematic cause I am free to derive the $[ \rightarrow ]$ part of the proof only if there is not $A$ in the definition. Then, is it redundant or not?

PS: Not sure you read my previous thread, but the all problem arises cause I am trying to use the software Proof Designer, which is a tool that can be use to implement the learning system presented in the book How to prove it: a structured approach to develop proof-skills. This software (and the books) are great, but the (positive!) side-effect is that human flexibility is not the point here.

Given a set $A$, a relation $R$ on $A$ is symmetric if $\forall x \in A \forall y \in A(xRy \rightarrow yRx)$.

Just for the curious reader, who is studying How to prove it and who is frustrated by the lack of results obtained with Proof Designer, I think I found a way to fix the problem.

We define the theorem that has to be proved in the following way: $$\forall x \in A \forall y \in A((x,y) \in A \times A \rightarrow (y,x) \in A \times A) \leftrightarrow A \times A = (A \times A)^{-1}$$.
Then we define $R=A \times A$ and the problem is solved.

PS: $A$ obviously is not redundant, so my question was simply wrong!